Obtenção de gel PLO contendo rutina para aplicação transdérmica : caracterização, estabilidade e atividade antioxidante - Andrade, Valléria Matos (2017)
Rutin is a flavonoid widely reported in the literature for its antioxidant properties, anti-inflammatory, vasoprotective, antithrombogen, among others. However, its low solubility in aqueous media reduces its bioavailability orally and, therefore, transdermal administration proves to be promising. Thus, the present work aimed to obtain, characterize and evaluate an activity and antioxidant activity of a gel. PLO (Pluronic Lecithin Organogel) containing rutin for transdermal administration.The analytical methodology for rutin quantification was developed and validated by high performance liquid chromatography (HPLC). Initially it was evaluated as an influence of the concentration of Polaxamer 407, obtained by the extrusion method with the aid of syringes, in front of the centrifugation test. The formulation that remained stable after the test was characterized by partical size determination, in vitro release study, in vitro skin penetration study, in vitro skin adhesion study. Also assessed for stability for 60 days at varying temperatures and at predetermined times, physico-chemical characteristics such as pH, density, viscosity and spreadability, as well as organoleptic characteristics, were evaluated. The antioxidant activity of the formulation was evaluated by the TRAP and TAR methods, comparing it with a positive control, Trolox. The results demonstrate that a formulation with higher concentration of Polaxamer is more stable and that is why it was characterized. The partical size were perfect for dermal administration. The formulation demonstrated controlled release of the drug after 24 hours, being able to permeate as deeper layers of the skin and to be absorbed into the systemic circulation, in addition to good adhesion to the skin surface. During the accelerated stability study, as formulations stored at low temperature, they underwent small variations in density, viscosity and spreadability relative to those stored at room temperature, while the pH remained stable throughout and favorable for application in skin. However, as observed variations were not sufficient to cause visual signs of instability. As for the antioxidant activity, a formulation showed greater activity in relation to the Trolox control and the free rutin, but it was not able to sustain an activity for a longer time, presenting a lower TAR value than Trolox. Thus, a chosen formulation has been shown capable of promoting a permeation of the rutin by transdermal route in a controlled manner, as well as being stable at an ambient temperature and having more significant antioxidant activity than the free rutin, and is therefore promising to administration of rutin by this route.